Can universities catalyze social innovation to support their own rapid decarbonization? Assessment of community and governance readiness at the University of California - Rebich-Hespanha, Stacy; Bales, Roger C. (Frontiers in Sustainability, 2023)
Universities aspire to lead on sustainable energy transitions, yet progress toward reducing their own emissions has been challenging. We assessed barriers and opportunities for engagement of University of California (UC) campus communities in stimulating more deliberate and rapid campus energy transformation, and our findings highlight the complexity of the socio-technical and governance systems that limit potential for transformative change for decarbonization. Through surveys, interviews, focus groups, and content analysis, we found strong interest among students, faculty, and staff in advancing decarbonization. We found a preference for local and on-campus solutions such as energy efficiency, behavioral change, renewable-energy production, and electrification, and much less support for market offsets and non-local investments. We also found that students and faculty had limited knowledge and sense of agency regarding campus-based decarbonization programs and options, which is consistent with the limited availability of data and information about these programs beyond the few who are directly involved. Weaving our findings with insights from social-innovation theory, we propose an action research agenda that conceives of university operations and governance systems as loci for socio-technical energy transition experiments. In alignment with higher education’s long-standing commitments to catalyzing social innovation, opening university energy operations and governance to inclusive, community-led collaborative experimentation has strong potential to create the conditions necessary to produce the social innovation so desperately needed for energy system transformation within universities and beyond.